Effects of Eco-Enzyme Dosage and Application Methods on Growth and Yield Components of Peanut (Arachis hypogaea L.) - Cut Mulia Sari; Budi Al Hadi; Bukhari Bukhari; Murtaza Murtaza (ITScience (Information Technology and Science), 2025)
Peanut (Arachis hypogaea L.) is a valuable legume crop whose productivity depends on effective and environmentally friendly nutrient management. Eco-enzyme, a liquid organic product obtained from the fermentation of organic waste, has potential as a sustainable agricultural input; however, information regarding its optimal dosage and application method for peanut cultivation remains limited. This study aimed to evaluate the effects of eco-enzyme dosage, application method, and their interaction on the growth and yield components of peanut plants. The experiment was conducted using a factorial randomized block design with two factors. The first factor was eco-enzyme dosage at four levels: 0, 10, 15, and 20 mL plant?¹. The second factor was the application method, consisting of soil drenching and foliar spraying. Observations included vegetative growth parameters and yield components. Data were analyzed using analysis of variance (ANOVA) followed by a least significant difference test at the 5% level. The results showed that the eco-enzyme dosage significantly affected plant height at 30 and 45 days after planting, whereas the application method alone did not significantly influence most of the observed variables. However, a significant interaction between dosage and application method was observed for plant height at 45 days after planting, number of empty pods, fresh pod weight, dry pod weight, and seed weight. Higher eco-enzyme dosages combined with appropriate application methods tended to improve yield performance. In conclusion, eco-enzyme influenced peanut growth and yield selectively, and its effectiveness depended largely on the interaction between dosage and application method